Clinical Validation of the Potential of Herbal Extract Blend in Alleviating the Stress and Related Conditions: A Randomized, Placebo-Controlled, Cross-Over Clinical Study - Vaidya, Dr. Vidyadhar; Ganu, Dr. Gayatri; Soman , Girish; Shinde, Renuka (International Journal of Innovative Research in Medical Science, 2024)
Background: The global rise in stress-related conditions has increased the demand for effective and safe interventions. This study aims to validate the efficacy of BacoZen™ blend tablets, an herbal blend of Ashwagandha extract and Brahmi extract, in alleviating stress. Methodology: A randomized, placebo-controlled, cross-over clinical trial was conducted with 64 subjects. Group A received BacoZen™ blend tablets for 4 weeks (Part I), followed by a 1-week washout period and placebo for 4 weeks (Part II). Group B received the interventions in reverse order. Assessments included perceived stress, cortisol, dopamine, sleep parameters, mood, fatigue, anxiety, and withdrawal symptoms. Results: The test group exhibited significant reductions in perceived stress (31.78%, 32.46%), cortisol levels, and improvements in dopamine levels, sleep quality, mood, fatigue and anxiety compared to the placebo group in both treatment parts. No adverse events or clinically significant changes in vital signs were reported, indicating excellent tolerability. The crossover design confirmed the intervention's consistent efficacy, independent of the sequence. Conclusion: BacoZen™ blend tablets containing herbal extracts Ashwagandha and Brahmi demonstrated robust and reproducible therapeutic effects in managing stress and anxiety, with an excellent safety profile. These promising results substantiate its potential as a safe and effective alternative to conventional interventions.